Exploring Digital Stories for Character Education: A Multivocal Literature Review - Surtinawati Surtinawati; E. Ngestirosa Endang Woro Kasih; Afrianto Afrianto; Harits Setyawan (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
Digital transformation in education has brought significant implications to Indonesian learning practices, but it still leaves complex conceptual, technological, and pedagogical challenges. This research aims to systematically explore the challenges and opportunities in the implementation of digital-based Indonesian learning, as well as evaluate the impact of digital platforms on motivation, language skills, and the effectiveness of learning tools. This study uses the Systematic Literature Review (SLR) method with a qualitative thematic synthesis approach based on 10 selected articles from the range of 2020 to 2025. The literature selection process follows the PRISMA 2020 flow, and data analysis is carried out through manual extraction of the key findings of each study. The results of the study show that the main challenges include low teacher digital literacy, a lack of integration of technology pedagogy, student unpreparedness in independent learning, and limited digital access and inclusivity. On the other hand, opportunities include the use of technology such as virtual reality, gamification, machine learning, and interactive media that can increase motivation and learning engagement. This study concludes that digital Indonesian learning requires a multidimensional theory-based approach to create an adaptive, inclusive, and transformative learning system.